Substrates coated with silver nanoparticles as a neuronal regenerative material - Alon N (Dove Medical Press, 2014)
Noa Alon,1,3,* Yana Miroshnikov,2,3,* Nina Perkas,2,3 Ifat Nissan,2,3 Aharon Gedanken,2,3 Orit Shefi1,31Faculty of Engineering, 2Department of Chemistry, 3Bar-Ilan Institute of Nanotechnology and Advanced Materials, Bar-Ilan University, Ramat Gan, Israel*These authors contributed equally to this workAbstract: Much effort has been devoted to the design of effective biomaterials for nerve regeneration. Here, we report the novel use of silver nanoparticles (AgNPs) as regenerative agents to promote neuronal growth. We grew neuroblastoma cells on surfaces coated with AgNPs and studied the effect on the development of the neurites during the initiation and the elongation growth phases. We find that the AgNPs function as favorable anchoring sites, and the growth on the AgNP-coated substrates leads to a significantly enhanced neurite outgrowth. Cells grown on substrates coated with AgNPs have initiated three times more neurites than cells grown on uncoated substrates, and two times more than cells grown on substrates sputtered with a plain homogenous layer of silver. The growth of neurites on AgNPs in the elongation phase was enhanced as well. A comparison with substrates coated with gold nanoparticles (AuNPs) and zinc oxide nanoparticles (ZnONPs) demonstrated a clear silver material-driven promoting effect, in addition to the nanotopography. The growth on substrates coated with AgNPs has led to a significantly higher number of initiating neurites when compared to substrates coated with AuNPs or ZnONPs. All nanoparticle-coated substrates affected and promoted the elongation of neurites, with a significant positive maximal effect for the AgNPs. Our results, combined with the well-known antibacterial effect of AgNPs, suggest the use of AgNPs as an attractive nanomaterial – with dual activity – for neuronal repair studies.Keywords: nerve regeneration, nanotopography, antibacterial material, neuroblastoma, gold nanoparticles, zinc oxide nanoparticles